The Effect of Inquiry-Based Learning on Students’ Critical Thinking Ability and Activeness in Reaction Rate Material - Latifah, Ulfa Nur; Suprihatiningrum, Jamil (Lectura : Jurnal Pendidikan, 2024)
Studying chemistry is more than just gaining knowledge; it is also about exploring new ideas and finding new ways to understand what we already know. However, most students participate less when studying chemistry. They tend to memorize the concept and think less critically to understand and obtain solutions to a problem. Reaction rate is material closely related to practicum, which requires students to think more critically and participate actively in obtaining information. This research aims to determine the effect of inquiry-based learning on students’ critical thinking skills and activeness in reaction rate material. The type of this research is Quasi Experiment. The research design used was a Pretest-Posttest, Non-Equivalent Control Group Design. The population of this research was class XI MIPA students. The sampling technique used was the cluster random sampling technique. Researchers used test instruments and observations as data collection techniques. The research results from the Mann-Whitney U test show that the significance value or Sig (2-tailed) is (0.001). If compared, the value will be smaller than alpha 0.05 (0.001 < 0.05); this shows that the hypothesis is accepted, and it can be concluded that there is a difference in critical thinking between the experimental group and the control group. The results of descriptive statistical tests on the observation sheet show that the average activity of experimental group students is higher than that of the control group in each indicator. Thus, the inquiry-based learning model influences students' critical thinking skills and activeness in reaction rate material.